Music, cosmology, and the politics of harmony in early China - Brindley, Erica, 1971- (SUNY series in Chinese philosophy and culture., 2012)
Winner of the 2013 Reading Committee Accolade for a Specialist Publication in the Humanities presented by the International Convention of Asia Scholars In early China, conceptions of music became important culturally and politically. This fascinating book examines a wide range of texts and discourse on music during this period (ca. 500-100 BCE) in light of the rise of religious, protoscientific beliefs on the intrinsic harmony of the cosmos. By tracking how music began to take on cosmic and religious significance, Erica Fox Brindley shows how music was used as a tool for such enterprises as state unification and cultural imperialism. She also outlines how musical discourse accompanied the growth of an explicit psychology of the emotions, served as a fundamental medium for spiritual attunement with the cosmos, and was thought to have utility and potency in medicine. While discussions of music in state ritual or as an aesthetic and cultural practice abound, this book is unique in linking music to religious belief and demonstrating its convergences with key religious, political, and intellectual transformations in early China.